Manifestly Haraway / Donna J. Haraway. - Haraway, Donna Jeanne (Posthumanities ;, 2016)
Electrifying, provocative, and controversial when first published thirty years ago, Donna Haraway's 'Cyborg Manifesto' is even more relevant today, when the divisions that she so eloquently challenges of human and machine but also of gender, class, race, ethnicity, sexuality, and location are increasingly complex. The subsequent 'Companion Species Manifesto', which further questions the human nonhuman disjunction, is no less urgently needed in our time of environmental crisis and profound polarization. 'Manifestly Haraway' brings together these momentous manifestos to expose the continuity and ramifying force of Haraway's thought, whose significance emerges with engaging immediacy in a sustained conversation between the author and her long-term friend and colleague Cary Wolfe.